1992
DOI: 10.1143/jjap.31.2760
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Dependence of Correlation between Plasma Emission Delay Time and Plasma Emission Intensity of Laser Breakdown Induced by a Particle

Abstract: Plasma emission delay time and plasma emission intensity of laser breakdown induced by a polystyrene particle in water were measured simultaneously. Short plasma emission delay time tended to correspond to high plasma emission intensity, as expected from the spatial and temporal profiles of the laser pulse power density. Particle size dependence of the correlation between the two parameters may serve in the measurement of the particle size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In a recent publication, two different LIBD systems and their applications were reviewed in detail (Kim & Walther, 2007). One was based on the optical detection of plasma flash using either a photomultiplier tube (Ajiro et al, 1992;Fujimori et al, 1992) or a charge-coupled 432 device (CCD) camera (Bundschuh et al, 2001a(Bundschuh et al, , 2005Hauser et al, 2002;Jung et al, 2006Jung et al, , 2007; J.W. Kim et al, 2008;Walther et al, 2002).…”
Section: Libd Systemsmentioning
confidence: 99%
“…In a recent publication, two different LIBD systems and their applications were reviewed in detail (Kim & Walther, 2007). One was based on the optical detection of plasma flash using either a photomultiplier tube (Ajiro et al, 1992;Fujimori et al, 1992) or a charge-coupled 432 device (CCD) camera (Bundschuh et al, 2001a(Bundschuh et al, , 2005Hauser et al, 2002;Jung et al, 2006Jung et al, , 2007; J.W. Kim et al, 2008;Walther et al, 2002).…”
Section: Libd Systemsmentioning
confidence: 99%
“…It is intuitively thought that total light emission generated during breakdown is proportional to the volume of a particle. However, it has been reported in current papers [6,7] that the total light emission varies with each breakdown. This study set out to determine the threshold intensity required to generate dense plasma when interacting with a small solid particle (SSP) suspended in air and its emission.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, in ordered to obtain in-situ information of colloids and microparticles in aquatic media, many experimental studies using LIBS have been reported (Kitamori et al 1988(Kitamori et al , 1989a(Kitamori et al , 1989bAjiro et al 1992;Fujimori et al 1992Ito et al 1995Nakamura et al 1996;Hotokezaka et al 2000;Yun et al 2001). The detection of polystyrene ultrafine particles (Kitamori et al 1988(Kitamori et al , 1989aAjiro et al 1992;Fujimori et al 1992), microparticle of CaCO 3 (Kitamori et al 1989), FeOOH (Ito et al 1995;Nakamura et al 1996) and Eu(OH) 3 (Hotokezaka et al 2000;Yun et al 2001) in water using LIBS has been reported for particle counting, elemental analysis and observation of generation of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of polystyrene ultrafine particles (Kitamori et al 1988(Kitamori et al , 1989aAjiro et al 1992;Fujimori et al 1992), microparticle of CaCO 3 (Kitamori et al 1989), FeOOH (Ito et al 1995;Nakamura et al 1996) and Eu(OH) 3 (Hotokezaka et al 2000;Yun et al 2001) in water using LIBS has been reported for particle counting, elemental analysis and observation of generation of precipitation. In our previous studies (Hotokezaka et al 2000;Nagasaki et al 2002aNagasaki et al , 2002b, we showed that LIBS technique was useful for in-situ analysis of particulate europium(III) in aquatic media and CaCO 3 particles in air.…”
Section: Introductionmentioning
confidence: 99%